تأثير استخدام وسيلة الفيديو لترقية مهارة الاستماع في المدرسة الثانوية الإنسان الكامل الإسلامية بنكولو. - Sutriyani; Arifin, Zainul; Rahmawati (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2024)
The researcher discussed "the effect of using video media to improve listening skills in Insan Kamil Islamic High School Bengkulu". The problems in this study are 1) What is the ability of listening skills in eighth grade students at Insan Kamil Bengkulu Islamic School before using video media?, 2) How is the use of video media for listening skills of eighth grade students at Insan Kamil Bengkulu Islamic School?, 3) How is the influence of video media in improving the listening skills of eighth grade students at Insan Kamil Bengkulu Islamic school?.The research methodology used is an experimental research methodology with a quantitative approach to field research, while the experimental research design is quasiexperimental, data collection tools in this study are tests, interviews, observations, and documents. Data analysis using spss 25 software for Normality Test, Homogeneity Test and T. The results of the study were 1) the ability of listening skills of eighth grade students of Insan Kamil Islamic High School Bengkulu before the use of video media was low with an average score in the control class of 64.4 and an experimental class of 62.3. 2) Use of video media for listening skills in eighth graders. consists of three stages: preliminary activities, core activities consist of three steps: assimilation, accommodation, equilibration, and final activities. 3) The ability of listening skills of eighth grade students at Insan Kamil Islamic High School Bengkulu after using video media is a sufficient predicate with an average score in the experimental class of 82.4 and a control class of 73.4 with less predicate.Then the result of the T test is 14.065 with a 2-tailed sig value of 0.00 and below 0.05, Ha is acceptable. Therefore, researchers concluded that there is an influence on the use of video media for listening skills of eighth grade students of Insan Kamil Islamic High School Bengkulu.